MicroRNA-101 Regulates 6-Hydroxydopamine-Induced Cell Death by Targeting Suppressor/Enhancer Lin-12-Like in SH-SY5Y Cells - Omura, Tomohiro; Nomura, Luna; Watanabe, Ran; Nishiguchi, Hiroki; Yamamoto, Kazuhiro; Imai, Satoshi; Nakagawa, Shunsaku; Itohara, Kotaro; Yonezawa, Atsushi; Nakagawa, Takayuki; Kunimasa, Junichi; Yano, Ikuko; et al. (Frontiers in Molecular Neuroscience, 2021)
Endoplasmic reticulum (ER) stress has been reported as a cause of Parkinson’s disease (PD). We have previously reported that the ubiquitin ligase HMG-CoA reductase degradation 1 (HRD1) and its stabilizing factor suppressor/enhancer lin-12-like (SEL1L) participate in the ER stress. In addition, we recently demonstrated that neuronal cell death is enhanced in the cellular PD model when SEL1L expression is suppressed compared with cell death when HRD1 expression is suppressed. This finding suggests that SEL1L is a critical key molecule in the strategy for PD therapy. Thus, investigation into whether microRNAs (miRNAs) regulate SEL1L expression in neurons should be interesting because relationships between miRNAs and the development of neurological diseases such as PD have been reported in recent years. In this study, using miRNA databases and previous reports, we searched for miRNAs that could regulate SEL1L expression and examined the effects of this regulation on cell death in PD models created by 6-hydroxydopamine (6-OHDA). Five miRNAs were identified as candidate miRNAs that could modulate SEL1L expression. Next, SH-SY5Y cells were exposed to 6-OHDA, following which miR-101 expression was found to be inversely correlated with SEL1L expression. Therefore, we selected miR-101 as a candidate miRNA for SEL1L modulation. We confirmed that miR-101 directly targets the SEL1L 3′ untranslated region, and an miR-101 mimic suppressed the 6-OHDA–induced increase in SEL1L expression and enhanced cell death. Furthermore, an miR-101 inhibitor suppressed this response. These results suggest that miR-101 regulates SEL1L expression and may serve as a new target for PD therapy.